Quantum Dots Theory and Applications - Stavrou, Vasilios N. (IntechOpen, 2015)
The book Quantum Dots - Theory and Applications collects some new research results in the area of fundamental excitations, decoherence, charge states, epitaxial techniques and photoluminescence experiments related to devices made with quantum dots. This book is divided in two sections. First section includes the fundamental theories on excitons, trions, phase decoherence, and charge states, and the second section includes several applications of quantum dots.